Legal Protection for Victims of Triangle Scheme Vehicle Buying and Selling Fraud (Case Study at the Bali Regional Police) - Ni Komang Putri Pratiwi; Nurianto Nurianto; Zuhro Nurindahwati (Journal Of Social Science (JoSS), 2025)
Vehicle sales fraud using the triangle scheme is an increasingly prevalent cybercrime, particularly on social media platforms. This scheme involves a fraudster acting as a fake intermediary who deceives both the buyer and seller simultaneously. This study aims to examine the forms of legal protection available for victims and identify the obstacles faced by the Bali Regional Police in addressing such cases. Using a normative-empirical legal research method with a legislative and sociological approach, the study found that legal protection is provided through Article 378 of the Criminal Code, Article 28(1) of the Electronic Information and Transactions Law, and the Consumer Protection Law. The results reveal a steady increase in triangle scheme fraud cases—28 in 2023, 37 in 2024, and 50 by mid-2025—primarily involving motorcycle transactions. Victims face significant obstacles, including difficulty identifying perpetrators, limitations in digital tracing infrastructure, and weak SIM card regulations. Additional challenges stem from low public legal awareness and cultural barriers. The study recommends reinforcing an adaptive and responsive legal protection system that accommodates the complexities of digital crime and improves victim support mechanisms.